A Correlational Study to Assess the Effect of Social Media Engagement on Body Image Among Adolescents in Selected School, Haryana, India - Anjali Samson; Vikas Sharma (International Journal of Community Health Nursing And Practices, 2025)
Social media has become an undeniable force in shaping modern social interactions, particularly among adolescents. Social media platforms are often criticized for perpetuating unattainable beauty ideals. These platforms frequently showcase images highlighting slimness, youth, and flawless skin, often manipulated by filters, photo editing tools, or even cosmetic surgery. These portrayals of "ideal" beauty can distort adolescents' sense of themselves, leading to increased body dissatisfaction. Objectives of the study were: (i) To assess social media engagement among adolescents, (ii) To assess the body image among adolescents, (iii) To find a correlation between social media engagement and its effect on body image among adolescents, and (iv) To find out the association between social media engagement and body image among adolescents and selected demographic variables. Method: The research method chosen for this study was quantitative. A sample of 300 adolescents (ages 13–19 years), in the selective school in Haryana, was selected by purposive sampling technique. Standardized questionnaire social media engagement scale (SMES-A), and Body Image Scale were used for data collection; Descriptive and inferential statistics were used for data analysis; and IBM SPSS version 28.0 was employed to calculate reliability and correlation coefficients. Result And Conclusion: The results revealed that 100% of adolescents reported using social media, with 57% using it daily and 39.33% using it hourly. Instagram (34%) and YouTube (32.66%) were the most popular platforms. The primary reasons for using social media included following celebrities (68.33%) and staying in touch with friends and family (23.33%). A weak positive correlation (r=0.133) was found between social media use and body image, regarding body image, approximately 115 participants (38.33%) reported dissatisfaction with their appearance, while 151 (50.33%) expressed concern about the abundance of body hair. Additionally, 192 adolescents (64%) wished they looked like celebrities, models, or athletes. The study found significant associations between body image and factors such as religion, income, residence, hobbies, and frequency of social media use. These findings suggest that while social media influences body image to some extent, other personal and demographic factors contribute more significantly.
Keywords: Adolescents; Assess; Correlational study; Effects; body image; social media engagement